Effects of Lactic Acid Bacteria on Microbial Metabolic Functions of Paper Mulberry Silage: A BIOLOG ECO Microplates Approach - Wang, Xuekai; Cao, Xinxin; Liu, Han; Guo, Linna; Lin, Yanli; Liu, Xiaojing; Xiong, Yi; Ni, Kuikui; Yang, Fuyu (Frontiers in Microbiology, 2021)
Lactic acid bacteria occupy an important position in silage microorganisms, and the effects of exogenous lactic acid bacteria on silage quality have been widely studied. Microbial metabolism has been proved as an indicator for substrate utilization by microorganisms. Paper mulberry is rich in free carbohydrate, amino acids and other components, with potential to be decomposed and utilized. In this study, changes of microbial metabolism characteristics of paper mulberry silage with Lactobacillus plantarum (LP) and Lactobacillus buchneri (LB) were studied using biolog ECO microplates. The results showed that, average well-color development (AWCD), Shannon diversity, Shannon evenness and Simpson diversity were affected significantly by the ensiling time. LB and LP indicated different behaviors in the early ensiling phase, and LB exhibited a higher AWCD than LP at 7d. Principal component analysis revealed that samples of CK, LB and LP initially clustered at 3d and then moved into another similar cluster after 15d. This study indicated that the method of microbial metabolic functions was applicable to evaluate the acceleration of additives on silage.